2020
DOI: 10.1016/j.jhtm.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Couchsurfing involvement in non-profit peer-to-peer accommodations and its impact on destination image, familiarity, and behavioral intentions

Abstract: This is a repository copy of Couchsurfing involvement in non-profit peer-to-peer accommodations and its impact on destination image, familiarity, and behavioral intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 91 publications
(66 reference statements)
4
56
0
Order By: Relevance
“…Older travelers tend to have revisit intentions to websites with which they are familiar. This study strengthens the findings from existing research that travelers tend to revisit a previous brand by perceiving positive emotions such as hedonic value, mental well-being, or familiarity [ 114 , 115 , 116 ]. In particular, Lambert-Pandraud, Laurent, and Lapersonne [ 93 ] reported that positive emotions such as familiarity elicited by close relationships with a supplier and a biased memory of positive features of a previously chosen option may affect older travelers’ repurchase intention.…”
Section: Discussionsupporting
confidence: 87%
“…Older travelers tend to have revisit intentions to websites with which they are familiar. This study strengthens the findings from existing research that travelers tend to revisit a previous brand by perceiving positive emotions such as hedonic value, mental well-being, or familiarity [ 114 , 115 , 116 ]. In particular, Lambert-Pandraud, Laurent, and Lapersonne [ 93 ] reported that positive emotions such as familiarity elicited by close relationships with a supplier and a biased memory of positive features of a previously chosen option may affect older travelers’ repurchase intention.…”
Section: Discussionsupporting
confidence: 87%
“…The digitalized life supported by advanced information and technology has nudged the development of shared brands, that is, not merely limited to information sharing (Kuhzady et al, 2020 ). The conceptualization of shared brands indicates further openness through which individuals can enjoy and participate in the production of service and products, such as houses, cars, and charge pals (Martin, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, the sudden outbreak of the COVID-19 pandemic has furthered a digitalized transformation of human interaction where there is a reported increase in the users of social media (Lep et al, 2020 ; Vanko et al, 2021 ). Meanwhile, social media can be utilized by companies to extend businesses to a wider audience with a global reach and affect the behavioral intention of consumers while engaging in their CSR initiatives (Bialkova and Te Paske, 2020 ; Kuhzady et al, 2020 ). However, through a review of a study, the academy concerning CSR practices lags behind the practices of CSR engagement through social media (Kesavan et al, 2013 ; Chu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, attitude accounts for a positive evaluation or negative assessment of a specific behavior in future. The abundant evidence in the existing literature indicates that attitude is the salient predictor of individuals’ behavioral intentions across different settings in the hospitality industry [ 24 , 28 , 45 , 52 ]. In the same vein, prior research supported this argument in consumers’ pro-environmental behavior.…”
Section: Literature Reviewmentioning
confidence: 99%